Parameter characteristic of desktop laser engraving kit machine: A review / NS Badrishah, N Sa’ude ... [et al.] - Badrishah, NS; Sa’ude, N; Ibrahim, M; Wahab, MS; Haq, R; Marwah, OMF; Khirotdin, RK (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
In today's modern age, laser engravings become the most promising technologies to be used in order to engrave or mark an object. This study will be focusing on the parameter characteristic use of a new technology desktop laser engraving kit machines on materials. The aim of the present work is to investigate the influence of the process parameters on the surface quality when machined by desktop laser engraving kit according to precise design of experiment to the materials. According to these design of experiment, we analyze the effect of these input to the output parameters. According to Yilbas [1], in the laser engraving process, the process parameters can be adjusted and tuned to achieve the quality of cut or engraved desired. However, if a different work piece material is used for engraving, all of these parameters may require re-adjustment, which consumes a considerable amount of time and effort and this is the motive driving the project at hand. Finally, this research has used some of the practitioner findings to further support the research evidence found from published sources in the literature review.